Construction of highly efficient heat conduction channels within expanded graphite/paraffin phase change composites and their thermophysical properties. (November 2022) - Dong, Qianwen; Sun, Bing; Dong, Zhijun; Tian, Yongsheng; Zhu, Hui; Yuan, Guanming; Cong, Ye; Li, Baoliu; Guo, Jianguang; Li, Xuanke
Abstract: Paraffin waxes (PW) are organic phase change materials (PCMs) that can be potentially applied for the storage/release of low-temperature latent heat and thermal management. However, they have serious liquid leakage and poor thermal conductivity, which greatly restrict their practical application. Although numerous studies have been conducted to address these problems, it is challenging to achieve phase change composites (PCCs) that are characterized by high thermal conductivity and excellent phase change behavior. Herein, we put forward a novel strategy for preparing expanded graphite (EG)/PW binary PCCs with EG loading varying in the range of 10–40 wt%. The method is developed by constructing graphite sheets with high orientation inside the PCCs following compression induction. The highly oriented graphite sheets provide channels for highly efficient heat transfer, which significantly improves the thermal conductivity of the resulting EG/PW PCCs. The in-plane thermal conductivities of the EG/PW PCCs are in the range of 10.7–49.7 W m −1 K −1 under 10–40 wt% EG loading conditions, much larger than those of the previously reported EG/PW PCCs with the same EG content. The EG/PW composites also exhibit excellent compatibility, uniformity, thermostability, reliability, and phase change behaviors. These remarkable properties make the EG/PW composites promising for application in thermal management and heat storage. This work provides an efficient and generic strategy for designing and constructing high-efficiency heat transfer channels within the PCCs using sheet-shaped fillers with high thermal conductivity. Graphical abstract: Highlights: Constructing graphite sheets with high orientation inside the PCCs via compression induction. The highly oriented graphite sheets provide channels for highly efficient heat transfer. The in-plane thermal conductivities of the EG/PW composites are in the range of 10.7–49.7 W m −1 K −1 . The EG/PW composites are promising for application in thermal management and heat storage.